Antibiotic Susceptibility Profile of respiratory pathogens obtained at tertiary care hospital from western Nepal - Subedi, Deepak; Devkota, Surya Prasad; Bhatta, Dharm Raj; Sharma, Binita Koirala; Paudel, Ashmita; Gurung, Krishna; Gautam, Damodar (Nepal Journal of Biotechnology, 2019)
The prevalence and drug resistance of the respiratory pathogens is increasing gradually in Nepal. However, their detail study is rare in the western region of Nepal. Hence, this study was carried out to know the incidence and antibiotic susceptibility profile of the respiratory pathogens obtained at a tertiary care center located at Pokhara. 139 pathogens were isolated from 460 clinical samples included. Significant pathogens were Gram-negative bacteria 94 (67.62%), followed by 28 (20.15%) Candida, and Gram-positive isolates 17 (12.23%). The growth rate was significantly higher for sputum samples in comparison to throat swabs. Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter were significant Gram-negative isolates while Staphylococcus aureus, Streptococcus pneumoniae, and Streptococcus pyogenes were Gram-positive pathogens. Sensitivity rate was higher for colistin and imipenem among Gram-negative isolates while lower sensitivity was for cefepime. Vancomycin was effective against all tested Gram-positive isolates while erythromycin and ciprofloxacin were less effective.